Mengeksplorasi Persepsi Mahasiswa: Implementasi Model Pembelajaran Reading, Questioning, and Answering dalam Perkuliahan Biologi Dasar - Pujiastuti, Indah Panca; Fausan, Muhammad Mifta (BIOMA: Jurnal Biologi dan Pembelajarannya, 2024)
The students' perception of the implementation of the Reading, Questioning, and Answering (RQA) learning model was still an essential domain to be explored further. Therefore, this study aimed to explore students' perceptions of the implementation of the RQA learning model in Basic Biology lectures. This descriptive research used an exploratory survey method. The respondents who participated were 57 students (30%) enrolled in the Basic Biology course at the Health Administration Study Program, Faculty of Health Sciences, Universitas Sulawesi Barat. The instrument used to collect data was a questionnaire consisting of 30 statements with four answer choices using the Likert scale. The data obtained from the research were analyzed descriptively. The study findings indicated that students' perceptions were at a slightly high level after the implementation of the RQA learning model in Basic Biology lectures.